Sustainable livelihood development of farmers in Manipur through participatory technology application - Sharam, Ranjit; Devi, Renuka; Singh, R K Sandeep; Singh, M Suraj; Shyamananda, K; Chahal, V P (Indian Farming, 2022)
.